The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1620/tjem.213.41
|View full text |Cite
|
Sign up to set email alerts
|

Ets-1 Proto-Oncogene as a Potential Predictor for Poor Prognosis of Lung Adenocarcinoma

Abstract: The protooncogene Ets-1 is a transcription factor that is known to regulate certain matrix metalloproteinases and plasminogen activator, which have been associated with malignant behaviors in solid carcinomas. We hypothesized that Ets-1 expression is also associated with tumor progression and a worse prognosis in lung carcinoma patients. To clarify the role of the Ets-1 proto-oncogene, the expression of Ets-1 in non-small cell lung carcinomas using 156 paraffin-embedded specimens was determined in surgically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
1
24
1
1
Order By: Relevance
“…7,8,26 ETS-1 is thought to be related to the growth of carcinoma cells by its regulation of the transcription of MMPsFMMP1, MMP3, MMP9 and uPA [6][7][8][9]18 ; these proteases are responsible for ECM degradation, which is a key event in invasion. 27 It induces endothelial cell proliferation and activation, which in turn results in angiogenesis, another potential mechanism of action for this protooncogene.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,26 ETS-1 is thought to be related to the growth of carcinoma cells by its regulation of the transcription of MMPsFMMP1, MMP3, MMP9 and uPA [6][7][8][9]18 ; these proteases are responsible for ECM degradation, which is a key event in invasion. 27 It induces endothelial cell proliferation and activation, which in turn results in angiogenesis, another potential mechanism of action for this protooncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Белок ETS1 контролирует уровни экспрессии множества ге-нов, включая факторы транскрипции, протеазы, гены клеточного цикла, гены, регулирующие апоптоз, цито-кины и факторы роста [32]. Повышенная активность ETS1 наблюдалась при РМЖ, РЛ, раке яичников, обо-дочной и прямой кишки и меланоме [33][34][35][36][37]. ETS1 сверхэкспрессируется при инвазивном РМЖ и корре-лирует с его плохим прогнозом [38].…”
Section: экспериментальные статьиunclassified
“…30 Aberrant ETS1 expression appears to be associated with the pathophysiology of some malignancies, [5][6][7][8][9] so it has been suggested that pharmacological inhibition of ETS1 transcriptional activity may prove useful as a novel anticancer strategy. Recent reports have suggested transcriptional silencing of ETS1 could efficiently suppress angiogenesis in pancreatic cancer.…”
Section: Potential Mechanisms Of Inhibition Of Tumor Cell Proliferatimentioning
confidence: 99%
“…4 ETS1 plays a role in the regulation of physiologic processes such as cell proliferation and differentiation, and there is much evidence suggesting important roles for ETS1 in carcinogenesis and progression of a wide range of malignancies, including pancreatic cancer. [5][6][7][8][9] Transcriptional silencing of ETS1 could suppress angiogenesis of pancreatic cancer efficiently. 10 Correlation between ETS1 overexpression and aggressive tumor behavior suggests that ETS1 may be an attractive molecular target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%